Acylcarnitines and Genetic Variation in Fat Oxidation Genes in HIV-infected, Antiretroviral-treated Children With and Without Myopathy. Issue 8 (13th July 2022) - Kirmse, Brian; Hobbs, Charlotte; Aaron, Lisa; Montepiedra, Grace; Summar, Marshall; Williams, Paige L.; Smith, Caitlin J.; Van Dyke, Russell; Yu, Chunli; Ryckman, Kelli K.; Borkowsky, William; ,
Abstract : Background: Mitochondrial toxicity resulting in myopathy and lactic acidosis has been described in antiretroviral (ARV)-exposed patients. We hypothesized that myopathy in HIV-infected, ARV-treated children would be associated with metabolic (acylcarnitines) and genetic (variants in metabolic genes) markers of dysfunctional fatty acid oxidation (FAO). Methods: Acylcarnitine profiles (ACP) were analyzed for 74 HIV-infected children on nucleoside reverse transcriptase inhibitor (NRTI)-containing ARV. Thirty-seven participants with ≥2 creatine kinase measurements >500 IU (n = 18) or evidence of echocardiographic cardiomyopathy (n = 19) were matched with 37 participants without myopathy. Single nucleotide polymorphisms (SNPs) in FAO genes were also evaluated. Results: Abnormal ACP was 73% (95% CI: 56%–86%) and 62% (95% CI: 45%–78%) in the myopathic and nonmyopathic groups, respectively. No significant association was found between myopathy and having an abnormal ACP (OR = 2.10, P = 0.22). In univariate analysis, a 1-year increase in NRTI use was associated with a 20% increase in odds of at least 1 ACP abnormality [OR (95% CI) = 1.20 (1.03–1.41); P = 0.02), and a 1-year increase in protease inhibitor use was associated with 28% increase in the odds of having at least 1 ACP abnormality [OR (95% CI) = 1.28 (1.07–1.52); P = 0.006). Three SNPs, all in the gene for the carnitine transporter ( SLC22A5 ), were associated with the cardiomyopathy phenotype. Conclusion: FAO appears to be altered in HIV-infected children with and without myopathy, but abnormal FAO does not fully explain myopathy in ARV-exposed children. Further study of SLC22A5 variation in ARV-exposed people is warranted carnitine transporter dysfunction-related cardiomyopathy may be treatable.